Pelatihan dan Pendampingan Pemrograman Python Dalam Meningkatkan Kompetensi Siswa SMKN 5 Palu - Fadjryani; Abdul Mahatir Najar; Juni Wijayanti Puspita; Aan Bin Mardi; Maulidyani Abu; Resnawati, Resnawati (Jurusan Farmasi FMIPA Universitas Tadulako, 2024)
Python programming is a multipurpose interpretive programming language with a design philosophy that focuses on code readability. Python is a language that combines capabilities with very clear code syntax and is equipped with the functionality of a large and comprehensive standard library. Python supports multiple programming paradigms. One of the features available in Python is that it is a dynamic programming language equipped with automatic memory management. This Community Service Activity is carried out by providing training material starting from a basic introduction to the Python programming language, basic rules for writing Python syntax, an introduction to variables and data types in Python, operators in Python, and learning structures and functions in Python. The mentoring process is also carried out to provide direct experience to students. This activity went well and received appreciation from the school, and the students hope that this activity can be continued so that students are able to apply Python programming well.